2019
DOI: 10.1053/j.semperi.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic interventions for the prevention and treatment of retinopathy of prematurity

Abstract: Retinopathy of prematurity (ROP), a significant morbidity in prematurely born infants, is the most common cause of visual impairment and blindness in children and persists till adulthood. Strict control of oxygen therapy and prevention of intermittent hypoxia are key in the prevention of ROP, but pharmacologic interventions have decreased risk of ROP. Various drug classes such as methylxanthines (caffeine), VEGF inhibitors, anti-oxidants, and others have decreased ROP occurrence. The timing of pharmacologic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 187 publications
1
12
0
Order By: Relevance
“…Each treatment demonstrated mechanistically distinct beneficial attributes, targeting inflammation, oxidants, or promoting growth, leading us to hypothesize that combining the treatments would lead to synergistic enhancement and optimization of their particular attributes. Since the etiology of OIR/ROP is complex and involves numerous mechanisms associated with oxidative stress, poor growth, and inflammation, we utilized a blend of oral antioxidant/anti-inflammatory/growth-promoting supplements to a non-invasive, topical ocular NSAID previously shown to be safe and effective in preterm infants for ROP [ 55 ], and in our OIR model [ 7 ]. While the mechanism of NSAID inhibition of angiogenesis is complex, studies show that NSAIDs have inhibitory effects on HIF 1α and von-Hippel-Lindau (VHL) [ 59 ], and exogenous prostaglandins partly reverses NSAID inhibition of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each treatment demonstrated mechanistically distinct beneficial attributes, targeting inflammation, oxidants, or promoting growth, leading us to hypothesize that combining the treatments would lead to synergistic enhancement and optimization of their particular attributes. Since the etiology of OIR/ROP is complex and involves numerous mechanisms associated with oxidative stress, poor growth, and inflammation, we utilized a blend of oral antioxidant/anti-inflammatory/growth-promoting supplements to a non-invasive, topical ocular NSAID previously shown to be safe and effective in preterm infants for ROP [ 55 ], and in our OIR model [ 7 ]. While the mechanism of NSAID inhibition of angiogenesis is complex, studies show that NSAIDs have inhibitory effects on HIF 1α and von-Hippel-Lindau (VHL) [ 59 ], and exogenous prostaglandins partly reverses NSAID inhibition of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, no single therapy has been proven to be successful without significant short- or long-term adverse effects. We have previously shown that combination treatment with systemic caffeine and topical ocular ketorolac resulted in prevention of severe IH-induced retinopathy in a rat model [ 5 , 6 , 7 ]. We have also shown that supplementation with either the antioxidant, coenzyme Q10 (CoQ10) or omega 3 polyunsaturated fatty acids ( n -3 PUFAs), targeting oxidants and/or growth deficits, were individually effective for ameliorating specific characteristics consistent with ROP [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROP, the leading cause of blindness in children, is an ocular manifestation in premature babies with limited and potentially invasive therapeutic options [ 10 , 35 ]. Halting ROP in premature children is critical for the prevention of severe ocular complications of the affected children that could eventually result in severe hypovision or complete blindness [ 36 , 37 , 38 ]. Herein, we have investigated the effects of the secondary BA, UDCA, and its glycine and taurine derivatives, GUDCA and TUDCA, in halting ROP-like features in mice subjected to OIR.…”
Section: Discussionmentioning
confidence: 99%
“…The eye is an organ which at the early stage of life is highly susceptible to changes in oxygen concentration. Vascularization begins in a 16-17-week-old fetus and is stimulated by various hormonal factors as well as “physiological hypoxia” [ 101 ]. Intense exposure to oxygen causes loss of vessels at the first stage, followed by neovascularization at the next stage.…”
Section: Neonatal Diseases Related To Ros and Intense Inflammationmentioning
confidence: 99%